Assessing The Characteristics of Elementary School Students' Mental Models in Understanding The Concept of Integers - Utami, Anita Dewi; Zainudin, M.; Noviana, Sa'in (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to reveal the characteristics of the mental model of elementary school students in understanding the concept of integers. The subjects in this study were selected based on outlier criteria or unique responses to a series of tests given to 30 students of the third grade of elementary school. As a result, two students were chosen as research subjects. The research data were collected through observation and interviews. Observation made by the researchers were direct observations, in which the researchers see and observe the activities of students in doing the test. In addition, the researchers also conducted interviews with research subjects. The results of the students' works were reviewed, and then interviews were conducted to clarify the students' answers. The results showed that the characteristics of elementary school students in understanding integers did not always move from the synthetic stage to the formal stage, but there were lower grade students who were able to solve contextual problems related to integers. The process of forming students' formal mental models can be seen when they solve the temperature rise problem by counting fingers and comparing them with the zero symmetry position between negative and positive integers.